Factors and cost associated with atopic dermatitis in Nevada. Issue 7 (2nd October 2020) - Johnson, Hadley; Anderson, Julia; Moonie, Sheniz; Gutierrez, Karen; Hogan, Mary Beth
ABSTRACT: Objectives : Atopic dermatitis, or eczema, is an inflammatory illness that impacts individuals of all ages. The cost of treating AD and the impact on the quality of life have not been well documented in the state of Nevada. This study seeks to fill this gap by identifying factors that impact the cost of AD in the state utilizing clinical and patient demographics. Methods : ANOVA with Bonferroni adjustment was performed using a large hospital utilization database to examine the cost of AD in the state of Nevada across all hospital settings. Results : Several significant factors were associated with the overall cost of AD in Nevada, including hospital setting type (outpatient vs. inpatient), physician type, region, AD diagnosis level, and age (p < 0.05). Stratified analysis was performed by setting type. In the inpatient setting, region, diagnosis level, and records with age listed between 0 and 5 years remained significant (p < 0.05). In the outpatient setting, physician type, region, and African American race remained significant (p < 0.05). Conclusions : Data from this study indicate that the AD cost burden is dependent on both demographic and clinical factors in the state of Nevada. These differences suggest that patients with AD may encounter higher costs depending on age, race, and clinical factors.